Membangun Desain Kemasan yang Mengusung Kebudayaan Indonesia pada Brand Madang Kebab Nusantara (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
In recent times, there has been a notable upswing in the economic development of Indonesia. This phenomenon has prompted Small and Medium Enterprises (SMEs) enthusiasts to seek innovative brand marketing strategies to strengthen the visual identity of their brands. Madang Kebab Nusantara is a nascent SME operating in the food industry and is currently in need of a robust brand identity amidst a competitive landscape within the same sector. In my capacity as a graphic designer with a solid educational background, I am entrusted with the responsibility of cultivating creative ideas in visual design, including logos, packaging, and mascots, to establish a professional image for the client's brand. Direct interaction with clients enables me to comprehend the needs of SMEs, articulate concepts, and deliver design solutions that align with the brand's essence, ensuring that the client's brand captures the attention of consumers in the market.